2007
DOI: 10.2337/db07-0856
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Association of Variants Near the HHEX, CDKN2A/B, and IGF2BP2 Genes With Type 2 Diabetes and Impaired Insulin Release in 10,705 Danish Subjects

Abstract: OBJECTIVE— In the present study, we aimed to validate the type 2 diabetes susceptibility alleles identified in six recent genome-wide association studies in the HHEX/KIF11/IDE (rs1111875), CDKN2A/B (rs10811661), and IGF2BP2 (rs4402960) loci, as well as the intergenic rs9300039 variant. Furthermore, we aimed to characterize quantitative metabolic risk phenotypes of the four variants. RESEARCH DESIGN AND METHODS— The variants were genotyped in the population-based Inter99 cohort (n = 5,970), the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
166
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 21 publications
(37 reference statements)
25
166
3
1
Order By: Relevance
“…Larger studies have also confirmed susceptibility loci within the SLC30A8, CDKN2A/B, IGF2BP2 and KCNJ11 genes as altering beta cell function, so larger studies may refine our initial estimates [7,11,12]. In conclusion, while individual susceptibility alleles only moderately alter pancreatic beta cell function, the risk is additively increased when risk alleles are combined.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Larger studies have also confirmed susceptibility loci within the SLC30A8, CDKN2A/B, IGF2BP2 and KCNJ11 genes as altering beta cell function, so larger studies may refine our initial estimates [7,11,12]. In conclusion, while individual susceptibility alleles only moderately alter pancreatic beta cell function, the risk is additively increased when risk alleles are combined.…”
Section: Resultsmentioning
confidence: 88%
“…The additive effects of the three risk variants were associated with a decrease in 30 min insulin response (p=4.17×10 −7 ). This was decreased by 43% in the 3.1% of the cohort with five or more risk alleles compared with the 3.2% that carried no risk alleles ( Although the other novel genes, CDKN2A/B, IGF2BP2, SLC30A8 and KCNJ11 have been shown to be associated with indices of pancreatic beta cell function in other studies [7,11,12], they did not reach statistical significance individually in our cohort [10]. However, when we included them in our additive model the relationships between increasing number of risk alleles and decreasing 30 min insulin response and decreasing beta cell glucose sensitivity still remained significant (p<0.001 and p=0.003, respectively).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Remarkably, second-phase insulin secretion remained intact. Previously, several studies have investigated the effects of novel susceptibility loci on insulin secretion as assessed by the OGTT [2-4, 6, 7] or IVGTT [2,[4][5][6]. These studies reported that these gene variants were associated with reduced insulin secretion but not with insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of these novel genes, FTO plays a role in childhood and adult obesity and the other five regions may play a role in pancreatic beta cell development and/or insulin secretion. Recent clinical results involving glucose tolerance tests indeed show that these variants affect insulin secretion, at least within the limitations of the tests used [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 97%